Learning in Madrasah based Pesantren during the Covid-19 Pandemic - Muh Mustakim; Nabila Miahara; Desy Khusna Nurmaida (STAI Hubbulwathan Duri, 2021)
Covid-19 is a pandemic that has been going on since the pre-pandemic period of the madrasah based pesantren is described in this paper. Researchers at MTs Ali Maksum conducted qualitative research. Triangulation was used to analyze the data gathered through interviews, observations, and documentation. The findings showed that the government-mandated online implementation of the direct learning model in pesantren-based madrasahs was successful. Based on evaluation results, there were limitations in the learning process starting from apperception to delivery of material, implementation, follow-up, and development of student competencies, resulting in problems in the next process. Before the pandemic, there was a gradual shift from face-to-face to online learning. It's also possible to combine the two. There are limitations to fully online learning, which is why pesantren-based madrasas consider blended learning as a solution.